College faith : 150 Christian leaders and educators share faith stories from their student days - Knott, Ron. (Berrien Springs, Mich. : Andrews University Press, 2002)
College, university and seminary presidents, and an outstanding roster of administrators, professors, and other Christian thought leaders, share moving and instructive personal stories of how God led them while they themselves were students in higher education.
Includes index.
Keywords: College students -- Religious life; Christian biography